Risk factors associated to the seroprevalence of Toxoplasma gondii in captive mammals from Carnivora and Primate Order - Navarro M., Dennis (2015)
The objective of this study was to determine the seroprevalence of T. gondii in captive wild animals of the Carnivora and Primates orders and identify the epidemiologic variables involved in its presentation. The study was conducted at the Patronato del Parque de las Leyendas Zoo, Lima, Peru. Blood samples were collected (Carnivora, n=49; Primates, n=52). In addition, samples were collected from 87 urban rodents and 18 domesticcats captured in the zoo. Surveys were done to identify potencial risk factors for each Order. Furthermore, morphometric parameters, estimated age, sex and body weight from rats and age and sex from cats were recorded. Indirect hemaglutination test was used for the diagnosis of T .gondii. Dilutions were prepared from 1:16 to 1:2048, considering positive a titre over 1/16. IgM antibodies were measured by using 2-Mercaptoethanol to determinate acute infections. The associations between the seroprevalence to T. gondii and the variables sex, origin, time in the institution and type of feeding were analyzed by the odds ratio (OR). The seroprevalence of T. gondii in captive mammals of the Carnivora and Primates orders was 87.8 and 80.8% respectively. Significant association (p<0.05) was only found between seroprevalence of T. gondii in primates and the type of feeds, where the omnivore diet had a significant risk factor (OR: 40.9) for the presentation of the infection. The frequency of anti-T. gondii antibodies in rodents (Rattus sp) and cats was25.3 and 77.8% respectively.